Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae) - Román, Nicolás Martínez; Archangelsky, Miguel (Zootaxa, 2017)
Mature larvae of two species of the riffle beetle genus Austrolimnius Carter & Zeck, 1929 are described and illustrated for the first time: Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941. A larval diagnosis for the genus is presented and both larvae are compared with each other and with the previously described larva of A. mucubajiensis Gómez & Bello, 2006. Comments on the species’ habitats are included.